EVALUASI PELAKSANAAN PERATURAN DAERAH KABUPATEN KAMPAR NOMOR 7 TAHUN 2012 TENTANG RETRIBUSI JASA UMUM (STUDI KASUS RETRIBUSI PELAYANAN PASAR AIR TIRIS) - Putri, Venti Dwi; Sahuri, Chalid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
In order activities or activities with noncurrent current market and also Kabupaten Kampar government issued a policy through Kabupaten Kampar Regulation No. 7 of 2012 About Charges for Services Sales Manager. Charges for services Sales manager is local charges are as Payment differences The services provided by the regional government to review the interests and objectives Utilization And Sales manager can be enjoyed by private bodies. The whole object is a levy has been used markets provided by local governments exploited by private law. Subject levy or an entity is a private enjoy exploit has been used market. Singer research theory using Willian N Dunn. The analysis of data used is descriptive qualitative method. Data source the data consist of primary data obtained Namely Yang From parties Kabupaten Kampar Office Market And Market UPTD Air Tiris. While secondary data namely data sourced from office data Kabupaten Kampar Office Market And Market UPTD Air Tiris. Data was collected using observation, interview and documentasi. Data analysis is the presentation of data analysis techniques, and withdrawal keseimpulan. Research shows that the implementation of Government policy on the market levy hearts Harvesting Pasar Tiris Tiris yet reached the level of effectiveness achieved is expected to review. Factors being sub office Market Barriers hearts implementation of Government policy is the lack of awareness required to pay retribution Market restribusi hearts, facilities and infrastructure adequately market the less and less resolute hearts clerk picked retribution. Among many traders deliberately for reasons to review not pay a fee set by the Government The Kampar. In addition officers picked restribusi not expressly indicated to Trader not want to pay compulsory retribution. Traders often complain because findings Sales of the Few. In addition reasons traders want to pay retribution is not because now merchants industry knows for what restribusi requested restribusi And where are allocated by the Government of Kampar regency. Keyword: Evaluation of Local Government Regulation, restribusi Market.